Extracellular matrix proteins in construction and function of in vitro blood-brain barrier models - Du, Feifan; Shusta, Eric V.; Palecek, Sean P. (Frontiers in Chemical Engineering, 2023)
The blood-brain barrier (BBB) is a highly impermeable barrier separating circulating blood and brain tissue. A functioning BBB is critical for brain health, and BBB dysfunction has been linked to the pathophysiology of multiple diseases such as stroke and Alzheimer’s disease. A variety of models have been developed to study the formation and maintenance of the BBB, ranging from in vivo animal models to in vitro models consisting of primary cells or cells differentiated from human pluripotent stem cells (hPSCs). These models must consider the composition and source of the cellular components of the neurovascular unit (NVU), including brain microvascular endothelial cells (BMECs), brain pericytes, astrocytes, and neurons, and how these cell types interact. In addition, the non-cellular component of the BBB microenvironment, such as the brain vascular basement membrane (BM) that is in direct contact with the NVU, also plays a key role in BBB function. Here we review the how extracellular matrix (ECM) proteins in the brain vascular BM affect the BBB, with a particular focus on studies using hPSC-derived in vitro BBB models, and discuss how future studies are needed to advance our understanding of how the ECM affects BBB models to improve model performance and expand our knowledge on the formation and maintenance of the BBB.